Determination of bacterial diversity in bulk soil and rhizospheres using molecular fingerprintings and phenotypic features - Tungao W. (International Digital Organization for Scientific Information, 2015)
The rationale of this study was to determine effects of root exudates on soil bacterial community within a particular period as well as on genetic diversity and phenotypic features of culturable bacteria. Total DNA was extracted directly from 3 soil samples including bulk soil, Brassica oleracea rhizosphere and Phaseolus vulgaris rhizosphere. Denaturing gradient gel electrophoresis (DGGE) profiles of PCR-amplified 16S rDNA of these soil samples were identical, suggesting that root exudates were unable to alter bacterial community within the 8-week planting period. As bacterial community could be retained after the enrichment of various compounds present in root exudates, this supports the hypotheses that soil contains a unique bacterial community that can adapt to environments and enrichment can affect only a portion of soil population. Even though plants did not cause detectable changes in bacterial community, they increased the numbers of culturable bacteria. Genetic diversity of bacterial isolates derived from 3 soil samples was investigated using enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC PCR). Dendrograms constructed from ERIC PCR profiles showed that genetic diversity of culturable strains from 3 soil samples was similar to one another. The 29 strains were obtained and used for plasmid profile and phenotypic feature studies. The 7 strains habored small plasmids range in number from 1 to 2 and size from 8 to 21 kilobase pairs (kb). The phenotypic features, including utilization of carbon and nitrogen sources, antibiotic resistance, vitamin requirement and production of indole acetic acid (IAA), were indistinguishable among strains from different soils. The effect of soil extracts on the growth of 6 representative bacteria was determined. The results show that soil extracts of both rhizospheres had the same effects on the growth of 6 strains tested, which differed from soil extract of bulk soil. © IDOSI Publications, 2012.